Association of psoriasis and periodontitis in the north Indian population - Sonam Singh Sachan; Shilpa Trivedi; Satyendra Kumar Sharma (Elsevier, 2024)
Background: Psoriasis is a chronic, non-communicable condition of the skin with an immune-mediated etiology. Periodontitis is a chronic inflammatory disease of the tooth-supporting tissues and is now recognized as an established risk factor for various systemic diseases. The present observational study aims to assess the prevalence of periodontitis and its related indices in individuals with psoriasis and to compare them with individuals without psoriasis. A cross-sectional case-control study was performed in a hospital setting, including 200 diagnosed cases of psoriasis and 200 age- and sex-matched healthy controls. Methods: The case group included patients diagnosed with psoriasis (defined as ICD-10 L40.0-L40.9) by a trained dermatologist. Controls included age- and sex-matched healthy individuals. After history-taking, a detailed dermatological and periodontal examination was done for all the enrolled subjects. The results were statistically analyzed using SPSS software. Results: The study group had a significantly higher mean GI, PI, PPD and CAL in comparison to the controls. Psoriasis patients had significantly greater scores for GI and PI (1.68 ± 0.61 and 1.57 ± 0.54, respectively) as compared to controls (1.48 ± 0.56 and 1.39 ± 0.60, respectively). Periodontitis was also found to be more prevalent among the cases. Stage II and Stage III periodontitis were found in 41.0 % of cases and 30.5 % of controls, while 12.5 % of cases and 6.0 % of controls had stage IV periodontitis. This difference was statistically significant. Conclusion: An association between psoriasis and periodontitis was found in the present study, as the individuals with psoriasis had a higher severity and prevalence of periodontitis.